Multiple disease resistance In roses against foliar and flower pathogens - A.P.SINGH, PRATIBHA SHARMA* and (Indian Phytopathology, 2002)
Powdery mildew (Sphaerotheca pannosa var.rosae) and black spot (Diplocarpon rosa e) are the major foliar, destructive and wide spread diseases in rose growing areas. Resistance breeding in roses is a major priority both for field and greenhouse cultivation. An evaluation of about 800 rose varieties, hybrids and selections during 1988-1998 revealed 210 promising varieties. None of the variety showed resistance against black spot and 83 varieties were recorded as moderately resistant. Out of 96 varieties against powdery mildew, 12 showed resistance and 36 moderate resistance.